2018
DOI: 10.1111/gwat.12630
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Methane Leakage from a Faulty Natural Gas Well into Fractured Tight Formations

Abstract: Horizontal drilling and hydraulic fracturing have enabled hydrocarbon recovery from unconventional reservoirs, but led to natural gas contamination of shallow groundwaters. We describe and apply numerical models of gas-phase migration associated with leaking natural gas wells. Three leakage scenarios are simulated: (1) high-pressure natural gas pulse released into a fractured aquifer; (2) continuous slow leakage into a tilted fractured formation; and (3) continuous slow leakage into an unfractured aquifer with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
(225 reference statements)
3
25
0
Order By: Relevance
“…Conversely, it is also possible that CH 4 ‐rich gas bypasses such pathways to shallower depths, depending on the locations of fluvial channels relative to failures of the cap rock integrity. This is similar to the migration of stray gas contamination from compromised natural‐gas wells through fractured tight formations discussed elsewhere in this issue (Moortgat et al ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, it is also possible that CH 4 ‐rich gas bypasses such pathways to shallower depths, depending on the locations of fluvial channels relative to failures of the cap rock integrity. This is similar to the migration of stray gas contamination from compromised natural‐gas wells through fractured tight formations discussed elsewhere in this issue (Moortgat et al ).…”
Section: Resultssupporting
confidence: 82%
“…This makes Osures capable of capturing the small‐scale onset of viscous and gravitational flow instabilities, if such fingering occurs (Moortgat ). The complex phase behavior of brine‐CO 2 and CH 4 is modeled using unique EOS‐based phase stability and phase split algorithms developed in prior work (see Li and Firoozabadi , ; Moortgat and Firoozabadi ; Moortgat et al , ). The governing equations for species transport in the two‐phase brine‐CO 2 and CH 4 system are provided in Soltanian et al (a).…”
Section: Model Developmentmentioning
confidence: 99%
“…Previous studies have indicated high permeability pathways, such as faults, leaky wells, or other breaches in aquitards, are probably required to allow for transport of contaminants NGWA.org J.C. McIntosh and G. Ferguson Groundwater 57, no. 5: 669-677 associated with HVHF to shallow aquifers Flewelling and Sharma 2014;Birdsell et al 2015;Moortgat et al 2018). The larger areal extent of the pressure anomaly also suggests that encountering a high permeability pathway is more likely with EOR than HVHF.…”
Section: Potential For Contaminationmentioning
confidence: 99%
“…Transport of formation waters and injected fluids over longer distances is more likely to occur with EOR than HVHF due to the longer time periods, despite the lower hydraulic head increases. Previous studies have indicated high permeability pathways, such as faults, leaky wells, or other breaches in aquitards, are probably required to allow for transport of contaminants associated with HVHF to shallow aquifers (Jackson et al ; Flewelling and Sharma ; Birdsell et al ; Moortgat et al ). The larger areal extent of the pressure anomaly also suggests that encountering a high permeability pathway is more likely with EOR than HVHF.…”
Section: Potential For Contaminationmentioning
confidence: 99%
“…Similar studies have begun to appear for identifying methane leakage from shale gas development, using either conceptual or numerical models to assess transport pathways and geochemical outcomes (17,18). Models and monitoring programs are often synergistic: Monitoring is necessary to calibrate, verify, and refine the conceptual and parametric representation of the subsurface embodied by the model, while the modeling helps to identify the sampling needs that are most important for reducing the uncertainties that matter most for both ongoing model improvements and management decisions.…”
Section: Direct Process Monitoring Neededmentioning
confidence: 99%